2008
DOI: 10.1177/0887302x07313625
|View full text |Cite
|
Sign up to set email alerts
|

Rural Consumers' Online Shopping for Food and Fiber Products as a Form of Outshopping

Abstract: The purpose of the research was to longitudinally investigate rural consumers' online shopping for food and fiber products as a function of satisfaction with local retailing and outshopping. Innovation diffusion theory was used to guide the research. Eight hundred seventy-nine rural consumers from 11 states completed surveys twice (in 2000 and 2003). Data were analyzed using structural equation modeling and analyses of variance. Dissatisfaction with local retailing in 2000 was a powerful driver of outshopping,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 69 publications
(112 reference statements)
1
38
0
Order By: Relevance
“…In his studies, he identify about 73% people stated that convenience as their main reason to use internet service. In further, he continued to conduct the same research again and he still found convenience as important factor where 76.5% people admit that shops online is convenient (Lennon et al, 2008). It is also support by (Sorce et al, 2005) that conveniences become the acceptable reason for consumer to shops online, especially for younger people (Sorce et al, 2005).…”
Section: Why Do People Choose To Shop Online?mentioning
confidence: 99%
See 4 more Smart Citations
“…In his studies, he identify about 73% people stated that convenience as their main reason to use internet service. In further, he continued to conduct the same research again and he still found convenience as important factor where 76.5% people admit that shops online is convenient (Lennon et al, 2008). It is also support by (Sorce et al, 2005) that conveniences become the acceptable reason for consumer to shops online, especially for younger people (Sorce et al, 2005).…”
Section: Why Do People Choose To Shop Online?mentioning
confidence: 99%
“…Most of the people that stayed in rural area will also face geographical distance problem. Owing to this factor, e-shopping is more beneficial and attractive to consumers who are living in rural area (Lennon et al, 2008). Nowadays, many people have busy lifestyles.…”
Section: Why Do People Choose To Shop Online?mentioning
confidence: 99%
See 3 more Smart Citations